Does hospital admission provide an opportunity for improving pharmacotherapy among elderly inpatients? - Daniela Oliveira de Melo; Sílvia Storpirtis; Eliane Ribeiro
ABSTRACT The purpose of the work was to assess the incidence of potential drug interactions (pDDI), major pDDI, and the use of potentially inappropriate medication (PIM) at hospital admission, during hospitalization, and at discharge to evaluate whether hospital admission provides an opportunity for improving pharmacotherapy in elderly patients at a University hospital that has a clinical pharmacist. A prospective cohort study was carried out using data from the medical records of patients admitted to an internal medicine ward. All admissions and prescriptions were monitored between March and August 2006. Micromedex(r) DrugReax(r) and Beers Criteria 2015 were used to identify pDDI, major pDDI, and PIMs, respectively. A comparison of admission and discharge prescriptions showed the following: an increase in the proportion of patients using antithrombotic agents (76 versus 144; p<0.001), lipid modifying agents (58 versus 81; p=0.024), drugs for acid-related disorders (99 versus 152; p<0.001), and particularly omeprazole (61 versus 87; p=0.015); a decrease in the number of patients prescribed psycholeptics (73 versus 32; p<0.001) and diazepam (54 versus 13; p<0.001); and a decrease in the proportion of patients exposed to polypharmacy (16.1% versus 10.1%; p=0.025), at least one pDDI (44.5% versus 32.8%; p=0.002), major pDDI (19.9% versus 12.2%; p=0.010) or PIM (85.8% versus 51.9%; p<0.001). The conclusion is that admission to a hospital ward that has a clinical pharmacist was associated with a reduction in the number of patients exposed to polypharmacy, pDDI, major pDDI, and the use of PIMs among elderly inpatients.